Acute Appendicitis Secondary to Appendiceal Endometriosis - João Paulo Nunes Drumond; André Luis Alves de Melo; Demétrius Eduardo Germini; Alexander Charles Morrell (Case Reports in Surgery)
Endometriosis in the vermiform appendix is a rare condition that affects women of childbearing age. The clinical picture can simulate inflammatory acute abdominal pain, especially acute appendicitis. Laboratory and imaging tests may assist in the diagnosis but are not conclusive. This article reports a case of acute appendicitis caused by appendiceal endometriosis for which laparoscopic appendectomy and diagnostic confirmation were performed after histopathological analysis.